2023
DOI: 10.3389/fpubh.2023.1122183
|View full text |Cite
|
Sign up to set email alerts
|

Association between heavy metals exposure and infertility among American women aged 20–44 years: A cross-sectional analysis from 2013 to 2018 NHANES data

Abstract: BackgroundInfertility has been confirmed as a significant medical and social problem. Heavy metal exposure refers to a risk factor for infertility, which is capable of damaging the reproductive system of males and females. However, heavy metal exposure and female infertility have rarely been investigated. The aim of this study was to analyze the association between heavy metal exposure and female infertility.MethodsA cross-sectional study using data from three cycles of the National Health and Nutrition Examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…23 Lead concentrations were associated with infertility in some categories but with no overall doseresponse pattern. 23 Compared with MIREC, mean concentrations of cadmium and mercury in NHANES were higher (0.45 μg/L for cadmium, 1.15 μg/L for mercury); however, concentrations of lead were the same (0.70 μg/dL). We found a decreased odds of infertility in the second tertile (0.50-0.77 μg/dL) of exposure for lead (OR 0.52, 95% CI 0.33-0.84), but not in those in the highest tertile (>0.77 μg/ dL) or when the exposure was modelled as a continuous variable.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…23 Lead concentrations were associated with infertility in some categories but with no overall doseresponse pattern. 23 Compared with MIREC, mean concentrations of cadmium and mercury in NHANES were higher (0.45 μg/L for cadmium, 1.15 μg/L for mercury); however, concentrations of lead were the same (0.70 μg/dL). We found a decreased odds of infertility in the second tertile (0.50-0.77 μg/dL) of exposure for lead (OR 0.52, 95% CI 0.33-0.84), but not in those in the highest tertile (>0.77 μg/ dL) or when the exposure was modelled as a continuous variable.…”
Section: Discussionmentioning
confidence: 94%
“…Another study including a larger sample of 838 participants from the 2013–2018 NHANES reported no association between blood concentrations of cadmium or mercury and self‐reported infertility 23 . Lead concentrations were associated with infertility in some categories but with no overall dose–response pattern 23 . Compared with MIREC, mean concentrations of cadmium and mercury in NHANES were higher (0.45 μg/L for cadmium, 1.15 μg/L for mercury); however, concentrations of lead were the same (0.70 μg/dL).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…As cadmium (Cd), lead (Pb), mercury (Hg), arsenic (As), di-2-ethylhexyl phthalate (DEHP), and bisphenol A (BPA), may alter several reproductive functions in women and have the toxicological aspect of fertility. [7][8][9][10][11] Observational studies have shown that lifestyle factors such as smoking, excessive consumption of alcohol and caffeine, and unbalanced nutritional habits exert a profound impacts on female reproductive health. [12][13][14] Some anthropometric indices have been proven to have side effects on female fertility.…”
Section: Introductionmentioning
confidence: 99%